Seasonal patterns of acute and recurrent idiopathic pericarditis - Hammer, Yoav (Clin Cardiol, 2017)
BACKGROUND: Idiopathic pericarditis is presumed to result from viral infection. The incidence rates of some viral infections have typical seasonal patterns. The data in the literature on a possible seasonal pattern of acute pericarditis are very limited. The mechanism and possible seasonality of recurrent episodes are not well established . HYPOTHESIS: The incidence of acute idiopathic pericarditis has a seasonal pattern. METHODS: The computerized database of a tertiary, university‐affiliated hospital was searched for all patients admitted with a first episode of acute idiopathic pericarditis between January 1, 2010 and December 31, 2015. Patients for whom a nonviral etiology for the pericarditis was identified were excluded. RESULTS: The final cohort included 175 patients (75% male) ages 19 to 86 years (median = 50.0 ± 18.2 years). The incidence of the disease was twice as high during the colder half of the year (October–March) than the warmer half, peaking in the first quarter (January–March, P = 0.001). This first‐quarter peak was observed in each of the 6 years examined. Comparison of the patients who acquired pericarditis during peak and nonpeak quarters yielded no differences in baseline characteristics, peak body temperature, white blood cell count, C‐reactive protein level, or frequency of myocardial involvement or liver enzyme elevation. No seasonal pattern was identified for recurrent episodes of pericarditis (n = 57). CONCLUSIONS: Acute idiopathic pericarditis appears to have a seasonal pattern with a distinct late winter peak. No seasonal pattern was identified for recurrent episodes.